Por uma escuta das vozes na escola: relações de gênero nos sons da educação física - Cáceres, Isabela Muniz dos Santos (2023)
With qualitative inspiration, the present research analyses a set of documents present in the bibliographies of civil service examinations from the public teaching network, in the initial training and in the service of teachers of Physical Education in the São Paulo State Network. Such documents are the Law of Guidelines and Bases, the National Curriculum Parameters, the São Paulo State Curriculum, the Common National Base, São Paulo Curriculum, as well as support materials for the Physical Education Curriculum. The work methodology, therefore, is placed in the perspective of documentary and bibliographical study, focusing on recent feminist and gender studies, as well as considering, through critical analysis, the legacy of the military dictatorship present in the field of physical education. In this way, it is a research that is justified by expressing and analysing the movement of tension of these elements, from which physical education in schools is built today. On the one hand, in the aforementioned tension, there are representative approaches to heteronormativity as a political regime, which silences everything that does not attend the dominant norms and standards; on the other hand, there is co-education and feminist ideas articulated to the bibliographies of competitions and continuing physical education. From this dynamic, a disputed educational scene emerges, where weaknesses and gaps appear, as well as achievements and challenges. If, in various ways, physical education is still based on medical, military and technical precepts, in other ways, a choir of other sounds emerges from the school scene, in the voices of the school, whether from and for Physical Education, whether from and for the whole society. In this sense, it is still necessary to explore the recent achievement of support materials for the Paulista Curriculum of Physical Education, which correspond to resistance to the traditional field of Physical Education, offering greater visibility of new subjects and constant combat to inequalities. These resistances and conquests arise as a result of the accumulation from the categories gender, race and generation arising from social movements and educational research and echoing inside the school and, from there, to the whole society.